THE FAMILY WATER NATURALIST : A practical expedition to the world of ponds, rivers and the sea shore - Angel, Heather, author; Wolseley, Pat, author; Angel, Heather, photographer; Eardley, Carolyn, editor (London : Michael Joseph, 1982)
Includes bibliographical references and index